Mediatization of society – Consequences for organizational communication - Raupp, Juliana (2005)
Mediatization serves as a starting point for developing a theoretical framework of external organizational communication. The overall importance of the mass media affects organizations: Organizations have to adapt to the logic of the mass media in order to gain attention in the media society. Thus, organizations make not only attempts to influence mass media; mass media also have an impact on organizations. The mutually dependent relationship between media and organizations is examined on the basis of a symbolic-interactionist communication theory. The structural characteristics of a mediated public sphere provide the backdrop for the complex relationships between mass media and organizations. Finally, the consequences of mediatization for organizations are discussed.